Comparison of the development of mouse embryos manipulatedwith different biopsy techniques - (:unkn) unknown (My University, 2016)
0

Preimplantation genetic diagnosis is the detection of inherited diseases and the sex of embryos before implantation in the practice of human medicine as well as in veterinary medicine. The introduction of experimental animal embryo biopsy techniques has been a milestone in the developmental process of preimplantation genetic diagnosis techniques. The aim of the present study was to evaluate in vivo and in vitro development of embryos after biopsy in an experimental mouse model and to perform comparisons across different biopsy techniques (blastomere biopsy and trophectoderm biopsy). At the end of the study, no significant difference was observed between the blastomere biopsy group and the control group in terms of in vitro development, embryo quality, and fetal development, whereas embryo quality and in vivo development were negatively affected in the trophectoderm biopsy group (P< 0.05).
Keywords: Ziraat Mühendisliği